2021
DOI: 10.1002/mc.23356
|View full text |Cite
|
Sign up to set email alerts
|

Sulforaphane covalently interacts with the transglutaminase 2 cancer maintenance protein to alter its structure and suppress its activity

Abstract: Type 2 transglutaminase (TG2) functions as an important cancer cell survival protein in a range of cancers including epidermal squamous cell carcinoma. TG2 exists in open and closed conformations each of which has a distinct and mutually exclusive activity. The closed conformation has GTP-binding/GTPase activity while the open conformation functions as a transamidase to catalyze protein-protein crosslinking.GTP-binding/GTPase activity is required for TG2 maintenance of the aggressive cancer phenotype. Thus, id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 65 publications
1
16
0
Order By: Relevance
“…To the best of our knowledge, this is the first explicit demonstration of the inhibition of GTP binding by these compounds, including those published previously ( 22a and 23a ). 21,34 It is interesting to note that these results appear to be aligned with those from another recent investigation, 20 in which we showed that sulforaphane, a very small irreversible inhibitor of TG2, is also able to partially inhibit GTP binding. Further studies are underway to determine the minimum steric bulk that is required to alter the conformational equilibrium of TG2 to completely abolish GTP binding.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first explicit demonstration of the inhibition of GTP binding by these compounds, including those published previously ( 22a and 23a ). 21,34 It is interesting to note that these results appear to be aligned with those from another recent investigation, 20 in which we showed that sulforaphane, a very small irreversible inhibitor of TG2, is also able to partially inhibit GTP binding. Further studies are underway to determine the minimum steric bulk that is required to alter the conformational equilibrium of TG2 to completely abolish GTP binding.…”
Section: Resultssupporting
confidence: 88%
“…14,[16][17][18] Extensive work has gone in to validating TG2 as a therapeutic target in the treatment of celiac disease, cancer, and kidney fibrosis. 19 Inhibitors of TG2 are extremely diverse, ranging from small molecules [20][21][22] to peptides. 23,24 Many of these inhibitors are designed to inactivate TG2's transamidase activity irreversibly, while some are also designed to suppress GTP binding by locking the enzyme in its open conformation.…”
Section: Introductionmentioning
confidence: 99%
“…This is important, since TG2 binding of GTP is required for TG2 procancer activity 4,52 . In addition, sulforaphane, a promising cancer prevention and treatment agent derived from cruciferous vegetables, covalently binds to TG2 to inhibit TG2 transamidase and GTP binding activities to reduce its ability to drive the cancer phenotype 53 . These findings suggest that TG2 is an important anticancer target and the treatment with TG2 specific inhibitors alone and in combination with agents that suppress related intracellular signaling pathways, or chemotherapeutic agents, may be useful treatment strategies.…”
Section: Discussionmentioning
confidence: 99%
“…As a promising anti-cancer agent harvested from dietary cruciferous vegetables, SFN exhibits effective preventive and therapeutic effects on cancers. 26,27 Previously, we have also reported the inhibitory effects of SFN on colorectal CSCs. 16 Here, consistent with the previous studies, we confirmed the inhibitory effects of SFN on colorectal CSCs, and further found that the SFN-induced ZO-1 expression dampened the nuclear translocation of β-catenin and CSC properties of CRC cells.…”
Section: Food and Function Papermentioning
confidence: 96%